Statistics on Public Expenditures for Economic Development (SPEED) - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
The 2019 Statistics on Public Expenditures for Economic Development (SPEED) database contains public expenditure data for 164 countries from 1980 to 2017 for ten sectors: agriculture, communication, education, defense, health, mining, social protection, fuel and energy, transport, and transport and communication combined as one sector. Indicators reported include percentage of sector expenditure in total expenditure, percentage of total expenditure to total gross domestic product, and per capita sector and total expenditure in constant prices. The data were compiled from multiple sources, including the International Monetary Fund, the World Bank, and national governments, and conducted extensive data checks and adjustments to ensure consistent spending measurements over time that are free of exchange-rate fluctuations and currency denomination changes. SPEED is a user-friendly tool that could help governments to better allocate their resources to be consistent with their policy objectives, and citizens’ needs and priorities. Because of the wide coverage of time periods, countries, and sectors, it could help policymakers and researchers to better understand the linkages between different types of public expenditure and development. It could also help examine historical trends and compare those to other countries.